Electrocatalytic CO2 Reduction over Atomically Precise Metal Nanoclusters Protected by Organic Ligands - Yang, Dan; Wang, Jiawei; Wang, Qiaojuan; Yuan, Zhaotong; Dai, Yihu; Zhou, Chunmei; Wan, Xiaoyue; Zhang, Qichun; Yang, Yanhui (ACS nano, 2022)
The electrochemical carbon dioxide reduction reaction (CO2RR) is a promising method to realize carbon recycling and sustainable development because of its mild reaction conditions and capability to utilize the electric power generated by renewable energy such as solar, wind, or tidal energy to produce high-value-added liquid fuels and chemicals. However, it is still a great challenge to deeply understand the reaction mechanism of CO2RRs involving multiple chemical processes and multiple products due to the complexity of the traditional catalyst’s surface. Organic ligand-protected metal nanoclusters (NCs) with accurate compositions and definite atom packing structures show advantages for revealing the reaction mechanism of CO2RRs. This Review focuses on the recent progress in CO2RRs catalyzed by atomically precise metal NCs, including gold, copper, and silver NCs. Particularly, the influences of charge, ligand, surface structure, doping of Au NCs, and binders on the CO2RR are discussed in detail. Meanwhile the reaction mechanisms of CO2RRs including the active sites and the key reaction intermediates are also discussed. It is expected that progress in this research area could promote the development of metal NCs and CO2RRs.